The Old Testament speaks ; v. 5 explaining the Old Testament as it was understood by its first readers - Fleming, Donald C. (Kowloon, Hong Kong Living Books for All)
Contents : v. 5 : Psalms.
Brethren writer. Donated by the author.
Keywords: Bible. O.T. -- introductions